Maggot Extract Interrupts Bacterial Biofilm Formation and Maturation in Combination with Antibiotics by Reducing the Expression of Virulence Genes - Mustafa Becerikli; Christoph Wallner; Mehran Dadras; Johannes M. Wagner; Stephanie Dittfeld; Birger Jettkant; Falk Gestmann; Heinz Mehlhorn; Tim Mehlhorn-Diehl; Marcus Lehnhardt; Björn Behr (Life, 2022)
Biofilms are aggregates of bacteria encased in an extracellular polymer matrix that acts as a diffusion barrier protecting the microbial community. Bacterial communication occurs by small signaling molecules called quorum sensing (QS) factors, which are involved in the activation of virulence genes and formation of biofilms. Larvae of the green bottle blowfly Lucilia sericata remove necrotic tissue by mechanical action (debridement) and proteolytic digestion. We produced a freeze-dried storable powder from larval extract and investigated its therapeutic effect on biofilms. Larval extract in concentrations of 6 and 12 mg/mL in combination with 0.5% antibiotics (≙50 U/mL penicillin and 50 μg/mL streptomycin) diminished free-floating (planktonic) Pseudomonas aeruginosa maintenance, while it showed no effect on Staphylococcus aureus and was not toxic to dermal cells. We established an ex vivo human dermal wound model. Larval extract in concentrations of 24 and 75 mg/mL in the presence of antibiotics (0.5%) significantly destroyed the biofilm stability of both P. aeruginosa and S. aureus biofilms. Furthermore, SEM analyses revealed crack and gap formations on P. aeruginosa. biofilm surface and decreased expression of P. aeruginosa biofilm maturation and virulence genes (lasR, rhlR and rhlA) was observed after treatment by larval extract in combination with antibiotics.